2003
DOI: 10.1002/ijc.11226
|View full text |Cite|
|
Sign up to set email alerts
|

Stage at diagnosis is a key explanation of differences in breast cancer survival across Europe

Abstract: We used multiple regression models to assess the influence of disease stage at diagnosis on the 5-year relative survival of 4,478 patients diagnosed with breast cancer in 1990 -1992. The cases were representative samples from 17 population-based cancer registries in 6 European countries (Estonia, France, Italy, Netherlands, Spain and UK) that were combined into 9 regional groups based on similar survival. Five-year relative survival was 79% overall, varying from 98% for early, node-negative (T1N0M0) tumours; 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
3
14

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(202 citation statements)
references
References 24 publications
(36 reference statements)
11
174
3
14
Order By: Relevance
“…These results are in agreement with the 5-year relative survival rate of 81.3% published in the EUROCARE-3 study from French population-based registries diagnosed in 1990 -1994 (Sant et al, 2003a). As highlighted in our study, survival varied significantly by county (Sant et al, 2003b). This is probably due to differences in the distribution of stage at diagnosis (Sant et al, 2003b) or to differences in the nature of the county (more urban or more rural) (Mitchell et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the 5-year relative survival rate of 81.3% published in the EUROCARE-3 study from French population-based registries diagnosed in 1990 -1994 (Sant et al, 2003a). As highlighted in our study, survival varied significantly by county (Sant et al, 2003b). This is probably due to differences in the distribution of stage at diagnosis (Sant et al, 2003b) or to differences in the nature of the county (more urban or more rural) (Mitchell et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…As highlighted in our study, survival varied significantly by county (Sant et al, 2003b). This is probably due to differences in the distribution of stage at diagnosis (Sant et al, 2003b) or to differences in the nature of the county (more urban or more rural) (Mitchell et al, 2006). We suggest that surveillance practices (a gynaecology consultation or a mammography during the years before diagnosis) as well as the circumstances of the mammography (screening or not) resulting from differences in the screening programmes in the counties may have influenced the stage at diagnosis.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies on the present data set analysed the effect of tumour stage on survival (Sant et al, 2003(Sant et al, , 2004. We used this detailed stage information -available in 92% of cases -to adjust for stage in the multivariable analysis of prognostic effects of morphology and receptor status.…”
Section: Discussionmentioning
confidence: 96%
“…We analysed data on a representative sample of 4478 breast cancer patients investigated in previous EUROCARE high-resolution studies on breast cancer (Sant, 2001;Sant et al, 2003). All had primary invasive breast cancer diagnosed in 1990 -1992 in the territories of 17 population-based cancer registries in six countries: Estonia (national registry); France (Bas-Rhin, Calvados, Côte d'Or, Doubs, Hérault, Isère, Somme, and Tarn); Italy (Firenze, Modena, Ragusa and Varese); Spain (Granada); the Netherlands (Eindhoven) and the UK (Mersey and Thames).…”
Section: Methodsmentioning
confidence: 99%
“…This appears to have a tangible influence on the point at which people decide to seek medical help. At a practical level, for example, some individuals who smoke have been reported to hold the belief that if they present with chest-related symptoms, health professionals will view them as being at fault (Sant et al, 2003). Interestingly, it has also been reported that even when people eventually do decide that they need to see a doctor, they may not couch their presenting complaints as being particularly significant, or directly indicative of anything serious.…”
Section: Introductionmentioning
confidence: 99%